Flexible Carbon Nanotube‐Epitaxially Grown Nanocrystals for Micro‐Thermoelectric Modules - Jin, Qun; Zhao, Yang; Long, Xuehao; Jiang, Song; Qian, Cheng; Ding, Feng; Wang, Ziqiang; Li, Xiaoqi; Yu, Zhi; He, Juan; Song, Yujie; Yu, Hailong; et al. (Advanced materials (Weinheim), 2023)
Flexible thermoelectric materials have attracted increasing interest because of their potential use in thermal energy harvesting and high‐spatial‐resolution thermal management. However, a high‐performance flexible micro‐thermoelectric device (TED) compatible with the microelectronics fabrication process has not yet been developed. Here a universal epitaxial growth strategy is reported guided by 1D van der Waals‐coupling, to fabricate freestanding and flexible hybrids comprised of single‐wall carbon nanotubes and ordered (Bi,Sb)2Te3 nanocrystals. High power factors ranging from ≈1680 to ≈1020 µW m−1 K−2 in the temperature range of 300–480 K, combined with a low thermal conductivity yield a high average figure of merit of ≈0.81. The fabricated flexible micro‐TED module consisting of two p–n couples of freestanding thermoelectric hybrids has an unprecedented open circuit voltage of ≈22.7 mV and a power density of ≈0.36 W cm−2 under ≈30 K temperature difference, and a net cooling temperature of ≈22.4 K and a heat absorption density of ≈92.5 W cm−2. This work presents an unconventional heteroepitaxial growth strategy to prepare high‐performance flexible and freestanding thermoelectric film with ordered and uniform microstructures. The integrated micro‐thermoelectric module based on the above films exhibits excellent energy harvesting and cooling performance, validating the potential of freestanding thermoelectric films for thermal energy efficient harvesting and management.